Auditor Reputation Under Different Negligence Regimes. (11th August 2015) - Bigus, Jochen
<x xml:space="preserve">Abstract</x> Do auditor reputation effects evolve the same way under precise negligence as under vague negligence? Or are there differences? We assume that investors update their beliefs on unobservable auditor quality when an auditor discloses an inaccurate report. We call this a reputation effect. A necessary condition for reputation effects to occur is that, ex ante, investors expect 'good' auditors to take more care than 'bad' auditors such that 'good' auditors are less likely to issue an inaccurate report. Consistent with empirical evidence, we assume that wealthier ('good') auditors tend to take more care than less wealthy ('bad') auditors. We find that under vague negligence, reputation effects will occur, inducing both types of auditor to increase the level of care taken. A 'good' auditor is likely to exert excessive care. Then, even in the absence of auditor risk aversion, a (properly defined) liability cap is necessary to induce efficient incentives. A contractual liability cap is preferable to a legally fixed liability cap. Under precise negligence, a 'good' auditor will exert the standard of due care. However, a 'bad' auditor will also do so if sufficiently wealthy. Consequently, ex ante, investors do not expect different levels of care to be taken or reputation effects to occur. A liability cap is not desirable. This paper highlights the importance of non‐legal sanctions in auditor liability. Finally, it links the 'reputation' and 'deep pocket' hypotheses, both of which have attempted separately in the past to explain the positive correlation between auditor size and auditor quality.